Unexpected hematologic malignancies after prostatectomy: Case report and literature review - İLBEY, YUSUF ÖZLEM; Karademir, Baris; Kisa, Erdem; Ozbilen, Mert Hamza; Bildirici, Cagdas; Karabacakoglu, Burak; Suelozgen, Tufan; Ilbey, YUSUF ÖZLEM; Kucuk, Ulku; Olgun, Aybuke (My University, 2021)
Introduction: Voiding symptoms, storage symptoms and post-voiding symptoms together constitute lower urinary tract symptoms (LUTS). Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults. The most common finding is lymphadenomegaly. Although infrequent, extranodal sites of involvement such as prostate can be detected. Mantle cell lymphoma (MCL) is a subtype of B cell non-Hodgkin lymphomas. Extranodal involvement findings such as prostate may be observed. In this case report, we will present a case in which we performed an open suprapubic prostatectomy (Freyer-s) and had CLL as a result of pathology, and a case whose pathology was MCL after transurethral resection of the prostate.